CDKL5 gene status in female patients with epilepsy and Rett-like features: two new mutations in the catalytic domain - Maortua Hiart; Martínez-Bouzas Cristina; Calvo María-Teresa; Domingo Maria-Rosario; Ramos Feliciano; García-Ribes Ainhoa; Martínez María-Jesús; López-Aríztegui; Puente Nerea; Rubio Izaskun; Tejada María-Isabel (BMC, 2012)
Abstract Background Mutations in the cyclin-dependent kinase-like 5 gene (CDKL5) located in the Xp22 region have been shown to cause a subset of atypical Rett syndrome with infantile spasms or early seizures starting in the first postnatal months. Methods We performed mutation screening of CDKL5 in 60 female patients who had been identified as negative for the methyl CpG-binding protein 2 gene (MECP2) mutations, but who had current or past epilepsy, regardless of the age of onset, type, and severity. All the exons in the CDKL5 gene and their neighbouring sequences were examined, and CDKL5 rearrangements were studied by multiplex ligation-dependent probe amplification (MLPA). Results Six previously unidentified DNA changes were detected, two of which were disease-causing mutations in the catalytic domain: a frameshift mutation (c.509_510insGT; p.Glu170GlyfsX36) and a complete deletion of exon 10. Both were found in patients with seizures that started in the first month of life. Conclusions This study demonstrated the importance of CDKL5 mutations as etiological factors in neurodevelopmental disorders, and indicated that a thorough analysis of the CDKL5 gene sequence and its rearrangements should be considered in females with Rett syndrome-like phenotypes, severe encephalopathy and epilepsy with onset before 5 months of age. This study also confirmed the usefulness of MLPA as a diagnostic screening method for use in clinical practice.